1978
DOI: 10.1080/00288233.1978.10427419
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in chemical composition of pasture

Abstract: As part of a study of seasonal variations in chemical composition of pasture herbage Ca, Mg, K, and Na concentrations, and the ratios KI (Ca + Mg) and CaIP, were determined by monthly samplings at seven sites in the lower North Island. Grass and clover components were harvested separately at six sites, and grasses, clovers, and "other species" (herbs) at the seventh. Sub.plots were harvested by hand shears, after which sheep were allowed to graze before the plots were enclosed until the next sampling date. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…There was little difference in P concentration in grasses and clovers, and the Mg concentration in clover was higher than in grasses. These results were similar to those of Metson & Saunders (1978).…”
Section: Mixed Pasture Analysessupporting
confidence: 81%
“…There was little difference in P concentration in grasses and clovers, and the Mg concentration in clover was higher than in grasses. These results were similar to those of Metson & Saunders (1978).…”
Section: Mixed Pasture Analysessupporting
confidence: 81%
“…Pasture Ca concentrations in both clovers and grasses exhibit strong seasonal trends as demonstrated in seven sites on the East Coast (Metson & Saunders 1978) and one site in Taranaki (Edmeades et al 1983b). Pasture Ca concentrations are lowest in the winter and spring and highest in the summer.…”
Section: Calcium Requirements For Pasturesmentioning
confidence: 94%
“…Using these criteria, Smith & Cornforth (range 0.10-3.26) and that 86% of the sites fell within the optimal range as defined above, 13% were in the "safe excess" range and only 1% were less than 0.30%. Cornforth (1984) subsequently adapted the criteria established by McNaught (1969McNaught ( , 1970 by adding an additional category and allowing for the fact that legumes have a higher requirement for Ca than grasses (Metson & Saunders 1978) (Table 2). Other workers have modified this data further by averaging the above data to provide criteria for mixed pasture samples.…”
Section: Calcium Status Of New Zealand Soilsmentioning
confidence: 99%
“…However, among the species they examined only Eustachys paspaloides and Andropogon schirensis showed enhanced silica accumulation with the growth period. Most other authors found lower concentrations of silica in plant leaves grown in the season [45][46][47]49]. We found concentrations depending on the phenological stage.…”
Section: Effect Of Season On Foliar Silica Accumulationmentioning
confidence: 47%